Contribution to the knowledge of Chinese Phasmatodea IV: Taxonomy on Medaurini (Phasmatodea: Phasmatidae: Clitumninae) of China - Ho, George Wai-Chun (Zootaxa, 2017)
This paper deals with the taxonomy of Chinese Medaurini with descriptions of two new genera, 14 new species and two new subspecies, proposal of two new combinations and report of two new records for China. A total of seven genera and 42 species are recognised in the tribe. Ten new species and two new subspecies from four recognised genera including Cnipsomorpha Hennemann, Conle, Zhang & Liu, 2008, Interphasma Chen & He, 2008, Medauroidea Zompro, 2000 and Parapachymorpha Brunner von Wattenwyl, 1893 are described. They are Cnipsomorpha bii sp. nov., C. daliensis sp. nov., C. maoershanensis sp. nov., C. wenxuani sp. nov., Interphasma elongatum elongatum sp. nov. & subsp. nov., I. elongatum parvum subsp. nov., I. huanglianshanense sp. nov., Medauroidea chenshuchuni sp. nov., Parapachymorpha dentata sp. nov., P. jinpingensis sp. nov. and P. sinica sp. nov. Two new genera, Neointerphasma gen. nov. and Neosinophasma gen. nov., are established. The former only includes Neointerphasma minutigranulatum sp. nov. The latter includes four species, N. biangulatum (Chen & Zhang, 2008) comb. nov. [transferred from Cnipsomorpha], N. tangliangi sp. nov., N. wenxuani sp. nov. and N. yunnanense sp. nov. A new combination is also suggested for Medauroidea nyalamensis (Chen, Shang & Pei, 2000) comb. nov. transferred from Ramulus Saussure, 1862. Parapachymorpha spiniger (Brunner von Wattenwyl, 1907) and Medauromorpha foedata (Brunner von Wattenwyl, 1907) are new records for China. Taxonomic keys are given to Cnipsomorpha, Interphasma, Medauroidea, Medauromorpha, Neosinophasma gen. nov. and Parapachymorpha.